Amazonian dark earths enhance the establishment of tree species in forest ecological restoration - Freitas, Anderson Santos de; Zagatto, Luís Felipe Guandalin; Rocha, Gabriel Silvestre; Muchalak, Franciele; Silva, Solange dos Santos; Muniz, Aleksander Westphal; Hanada, Rogério Eiji; Tsai, Siu Mui (Frontiers in Soil Science, 2023)
Deforestation of areas for agriculture and cattle breeding is the leading cause of ecological degradation and loss of biodiversity. The solution to mitigate these damages relies on techniques that improve soil health and the microbial quality of these degraded areas. Here, we demonstrate that the high nutrient and microbiological contents of Amazonian Dark Earths (ADE) can promote the development of trees used in ecological restoration projects. We used degraded soil from crops as control and ADE from the Central Amazon to conduct the experiment, using 20% of ADE as inoculum in degraded agricultural soil. Our goal was to assess whether a small amount of ADE could promote changes that improve plant development similar to its growth under a 100%ADE. We simulated conversion from pasture to forest restoration area by planting U. brizantha in all pots. After 60 days, we removed it and planted Cecropia pachystachya, Peltophorum dubium, and Cedrela fissilis. Our results demonstrated that both 20%ADE and 100%ADE treatments increased pasture productivity and, consequently, soil carbon stock. Also, in these treatments, P. dubium and C. fissilis had better growth and development, with 20%ADE plants showing a performance similar to those planted in 100%ADE. Both 20%ADE and 100%ADE showed similar numbers of taxa, being significantly higher than in the control soil. The 20%ADE was sufficient to increase significantly the microbial richness in the soil, providing several beneficial microorganisms to all tree species such as Pedomicrobium, Candidatus Nitrososphaera, and members of Paenebacillaceae. Nevertheless, C. pachystachya, a common pioneer tree in the Amazonian Forest showed a small response even to 100%ADE with a corresponding lower taxa number than the other two species. In conclusion, we point out that microbial structure remains very similar among plants but dissimilar among treatments, highlighting the role of ADE as an enhancer of plant development and beneficial microbiota enrichment in the rhizosphere. The use of 20%ADE was sufficient to alter the microbial community. Therefore, we believe our data could contribute to speeding up forest restoration programs by adopting new biotechnological approaches for forest restoration ecology.